Aktivitas Anti-Angiogenik Alpukat dan Minyak Sawit dalam Nanoemulgel Melalui Uji Membran Korioallantoik - Putri Giri Anjani; Hariyadi Dharmawan Syahputra; Edy Fachrial; Reghita Claudia Manalu; Iksen Iksen (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Angiogenesis is a fundamental hallmark of cancer progression and metastasis, and it could be prevented through chemomedication or natural products. Natural lipid-based bioactive incorporated into advanced drug delivery system have gained increasing attention for their full potential to modulate tumor/cancer asssociated agiogenesis. Avocado oil and crude palm oil are rich in bioactive lipid fraction with reported antioxidant and antiproliverative properties; however their comparative antiangiogenic efficacy when formulated as nanoemulgel systems remains unexplored. This study aimed to comparatively evaluate the antiangiogenic activity of avocado oil and crude palm oil bioactive compoun formulated ini nanoemulgel using Chorioallantoic Assay Membrane as model Avocado and crude palm oil formulated in nanoemulgel drug delivery systems with high emulsification and gel incorporation. Physiochemical properties from nanoemulgel gave a good results in stability especially in F5 with particle size of 280 nm and optimum viscousity to be 16.652 mPas at 100 rpm. The appearance of the formula was yellowish white with expectable pH range from 5.3 to 6.3. The optimal formulation has good spreadability coefficient and, good antiangiogenic activity also measured in decrease of blood vessel count around 34.5% and erytrocyte presents in edothelium. This study report the antiangiogenic effect of from natural lipid based bioactive such as avocado oil and crude palm oil have a potential candicate for future anti cancer therapy.